Responsibility for implicit bias - Holroyd, Jules (Wiley, 2012)
Philosophers who have written about implicit bias have claimed or implied that individuals are not responsible, and therefore not blameworthy, for their implicit biases, and that this is a function of the nature of implicit bias as implicit: below the radar of conscious reflection, out of the control of the deliberating agent, and not rationally revisable in the way many of our reflective beliefs are.